Comparing the mechanical and expected microstructural properties of (TIG) spot welding and resistance spot welding in automobile body restoration - Azaldin Alhaj Kozam; Mustafa I. Elshbo; Hesham Eshabani; Mohamed Saraj; Taghrid Gredish (African Journal of Advanced Pure and Applied Sciences, 2026)
Resistance spot welding is widely used in automobile industries due to its low cost, quality, and ease of implementation. In spite of that, the process often faces limitations related to the accessibility and variations in joint strength relative to the original manufacturing when performing restoration. The purpose of this study is to overcome these difficulties by comparing the mechanical and expected microstructural properties of TIG spot welding to offer a good alternative. This comparison includes peel testing, tensile testing, shear testing, and hardness testing. The results showed the welded dimensional nugget size is comparable to that produced by resistance spot welding, and TIG-spot welded samples showed a lower hardness but a higher tensile and shear strength. These results suggest future optimization of the parameters to achieve accurate weld spot sizes comparable to resistance spot nugget size or implant the same processes in an automated TIG welding machine.